TANGGUNG JAWAB TOUR LEADER DI PT. AISYAH PERDANA TOUR AND TRAVEL - Dhea Prisky Nadimisia; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Tour Leader is the most important role in a Travel Agency. Tour Leader has a responsibility to supervise the tour from the first departure till the end of the trip. This research aims to find out more about the implementation of the responsibilities of a tour leader. This research uses a qualitative method with a descriptive approach to describe the real situation by collecting information data from the field. The key informants from this research are 1 financial division staff who also serves as one of the tour leaders, and also 2 other tour leaders. The data collection methods used in this research are observation, interviews, documentation and also documentation studies. Based on the results of the research, it can be infered that the tour leader at PT. Aisyah Perdana Tour And Travel has done a good job. Tour leaders have to understand the Standard Operating Procedures (SOP) that have been established and also carry out the process of carrying out these responsibilities properly. Keywords: Implementation, responsibility, Tour Leader.